2011
DOI: 10.1002/clen.201000410
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clam Ruditapes philippinarum as Heavy Metal Bioindicators Using NMR‐Based Metabolomics

Abstract: Research Article Assessment of Clam Ruditapes philippinarum as Heavy Metal Bioindicators Using NMR-Based MetabolomicsThere are mainly distributed three pedigrees (White, Liangdao Red, and Zebra) of Manila clam Ruditapes philippinarum in Yantai population along the Bohai marine and coast. However, the biological differences to environmental stressors have been ignored in toxicology studies, which could lead to the distortion of biological interpretations of toxicological effects induced by environmental contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…When the adductor muscle was used as the target organ, White clams could be a preferable bioindicator of the pollution monitoring for dissolved mercury compared with the other two clam species, i.e. Liangdao Red and Zebra (Liu et al, 2011d); while, when digestive gland tissue was used as the target organ, Liangdao Red clams exhibited more sensitive disturbances to the mercury exposure (Liu et al, 2011e). …”
Section: The Situation Of Different Speciesmentioning
confidence: 99%
“…When the adductor muscle was used as the target organ, White clams could be a preferable bioindicator of the pollution monitoring for dissolved mercury compared with the other two clam species, i.e. Liangdao Red and Zebra (Liu et al, 2011d); while, when digestive gland tissue was used as the target organ, Liangdao Red clams exhibited more sensitive disturbances to the mercury exposure (Liu et al, 2011e). …”
Section: The Situation Of Different Speciesmentioning
confidence: 99%
“…Polar metabolites in the adductor muscle tissues of clams were extracted by the modified extraction protocol as described previously (Zhang et al, 2011a;Liu et al, 2011a). Briefly, the adductor muscle tissue (ca.…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…Marine bivalves accumulate osmoprotectants or osmolytes such as betaine, homarine and dimethylglycine to maintain osmotic balances and stabilities of cytomembrane under environmental stress (Shen et al, 2002). Zhang et al (2011c) and Liu et al (2010) found the similar phenomenon in bivalve Ruditapes philippinarum exposed to heavy metals.…”
Section: Effects Of Tbbpa Treatment On the Metabolome Of Gills In Malmentioning
confidence: 57%